RNA-Seq Technology Reveals the Mechanism of SDT Combined With Novel Nanobubbles Against HCC - Shang, Haitao; Chen, Yichi; Wang, Chunyue; Zhang, Shentao; Wu, Bolin; Liang, Xitian; Liu, Zhao; Wang, Qiucheng; Cheng, Wen (Frontiers in Molecular Biosciences, 2022)
Sonodynamic therapy has been widely used in the treatment and research of hepatocellular carcinoma. A novel targeted nanobubbles complex mediated with HMME and LND was structured as a sensitizer, characterized the properties, and studied the therapeutic effect on hepatocellular carcinoma. The complexes can promote the apoptosis of hepatocellular carcinoma cells and work better in combination with sonodynamic therapy. The differential expression of multiple types of RNA in hepatocellular carcinoma with sonodynamic therapy could be identified accurately with high throughput RNA sequencing. The differential expressions of mRNA, lncRNA, and circRNA were analyzed by RNA-Seq. The enrichment analyses (Go and KEGG) prompted the meaningful genes and pathways in the process of sonodynamic therapy in hepatocellular carcinoma cells. HMME-LND@C3F8-NBs conjugated with ultrasound are confirmed efficiently for inhibiting the development of hepatocellular carcinoma cells, and it is a combination of multiple genes and mechanisms.